2021
DOI: 10.1029/2020jc016990
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Shelf Circulations Under Multiple River Discharges in the East China Sea

Abstract: Marginal seas are primary fields for land-ocean interaction. Water mass and dissolved or suspended substances from both riverine and oceanic sources are transported and mixed, producing a highly dynamic and heavily productive area. It is reported that shelf ecosystems (tropical and non-tropical) primary productions are 8.37 × 10 15 gCyr −1 that supports 59.5% of primary production required to sustain world fisheries (Pauly & Christensen, 1995). Meanwhile, the continental shelves provide 90% of the global marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 99 publications
(106 reference statements)
2
10
0
Order By: Relevance
“…At the surface the upper 10 m is occupied by the coastal water. Since the ZMCC water mass is the coldest, it formed the colder and less saline middle mixed layer between 10 and 30 m. The warmer SCSWC water mass occupied the lower part of the water column below 30 m. Similar water mass structures have been described in previous studies in the northern TS and the ECS (Du and Liu, 2017;Wu et al, 2021). Within this overall setting, along the transport route of the ZMCC, the colder and more saline water at f and g than at e and h (Figures 2C,E) might be caused by coastal upwelling as described by Liu et al (2019).…”
Section: Discussionsupporting
confidence: 81%
“…At the surface the upper 10 m is occupied by the coastal water. Since the ZMCC water mass is the coldest, it formed the colder and less saline middle mixed layer between 10 and 30 m. The warmer SCSWC water mass occupied the lower part of the water column below 30 m. Similar water mass structures have been described in previous studies in the northern TS and the ECS (Du and Liu, 2017;Wu et al, 2021). Within this overall setting, along the transport route of the ZMCC, the colder and more saline water at f and g than at e and h (Figures 2C,E) might be caused by coastal upwelling as described by Liu et al (2019).…”
Section: Discussionsupporting
confidence: 81%
“…The CMEMS was used to act as our data for modeling because CMEMS assimilates a number of observation data sources, and previous findings indicated that the data assimilation technique can produce a reliable dataset (Edwards et al, 2015;Martin et al, 2015). Indeed, numerous studies employed the CMEMS to evaluate their observational data or produced ocean model in ECS and South China Sea (Lin et al, 2017;Lee et al, 2020;Sun et al, 2020b;Kok et al, 2021;Wu et al, 2021). Three topographic variables and six oceanographic variables were extracted for each position and date of the survey dataset, all variables were downscaled using a bilinear interpolation to match our fisheries data.…”
Section: Environmental Datamentioning
confidence: 99%
“…On the other hand, the river discharge also affects the stratification, instabilities, shelf circulation and dynamics at the submesoscale over the shelf, which is relevant to the ecosystem and biogeochemical processes. Large river plume plays a significant role in regulating the shelf circulation, which intensifies the cross-shelf exchange (Wu et al, 2021). River outflow can also enhance the submesoscale currents by increasing lateral buoyancy gradients but suppresses them by decreasing the boundary layer depth (Barkan et al, 2017).…”
Section: Impact Of River Discharge On the Shelf Circulationmentioning
confidence: 99%
“…Previous studies have used numerical models to trace the riverine freshwater by releasing dyes into the rivers in many coastal regions, such as the New York Bight (Zhang et al, 2010), the Rhine Region (Rijnsburger et al, 2021), the South Brazilian Bight (Marta-Almeida et al, 2021), the Yangtze River estuary (Yu et al, 2020;Wu et al, 2021), and the Great Barrier Reef (Colberg et al, 2020). Three-dimensional structure and evolution of the river plumes have been presented in these numerical simulations.…”
Section: Introductionmentioning
confidence: 99%